Laboratory and microstructural tests on the detection and prediction of AAR - Santos Silva, A. (2011)
LNEC has been involved in research dealing with alkali-aggregate reactions for the past 20 years. In recent years, the research has been directed at identifying the magnitude of the problem in Portugal, identifying rock types which may be potentially reactive, determining the influence of supplementary cementing materials to counteract the expansion associated to AAR and the continuous improvement of the methodologies to prevent this deleterious reaction in new concrete constructions. International and national workshops and seminars on concrete durability, and particularly related to the concrete degradation by alkali-aggregate reactions, have been held to disseminate the information. One integral part of this research work has been the transfer of technology to the universities and concrete industry in the subjected area. This presentation is a perfect example of the cooperation between LNEC and the Portuguese Universities in this specific topic related with the laboratory and microstructural tests on the detection and prediction of AAR.